Low-pressure RF remote plasma cleaning of carbon-contaminated B4C-coated optics - Moreno Fernández, H; Thomasset, M; Sauthier, G; Rogler, D; Dietsch, R; Barrett, R; Carlino, V; Pellegrin, E (Proceedings of SPIE, the international society for optical engineering, 2017)
Boron carbide (B4C) - due to its exceptional mechanical properties - is one of the few existing materials that can withstand the extremely high brilliance of the photon beam from free electron lasers (FELs) and is thus of considerable interest for optical applications in this field. However, as in the case of many other optics operated at modern accelerator-, plasma-, or laser-based light source facilities, B4C-coated optics are subject to ubiquitous carbon contaminations. These contaminations - that are presumably produced via cracking of CHx and CO2 molecules by photoelectrons emitted from the optical components - represent a serious issue for the operation of the pertinent high performance beamlines due to a severe reduction of photon flux and beam coherence, not necessarily restricted to the photon energy range of the carbon K-edge. Thus, a variety of B4C cleaning technologies have been developed at different laboratories with varying success [1]. Here, we present a study regarding the low-pressure RF plasma cleaning of a series of carbon-contaminated B4C test samples via an inductively coupled O2/Ar and Ar/H2 remote RF plasma produced using the IBSS GV10x plasma source following previous studies using the same RF plasma source [2, 3]. Results regarding the chemistry, morphology as well as other aspects of the B4C optical coatings and surfaces before and after the plasma cleaning process are reported.